Melatonin Modulates ZAP70 and CD40 Transcripts via Histone Modifications in Canine Ileum Epithelial Cells - Jian Hong; Saber Y. Adam; Shiqi Wang; Hao Huang; In Ho Kim; Abdelkareem A. Ahmed; Hao-Yu Liu; Demin Cai (Veterinary Sciences)
Melatonin (MLT), produced by the pineal gland and other tissues, is known for its anti-inflammatory effects, particularly in regulating inflammatory markers and cytokines in intestinal cells. Our study aimed to investigate how MLT influences the expression of inflammatory genes through histone modification in canine ileum epithelial cells (cIECs). In our experiment, cIECs were cultured and divided into a control group (CON) and an MLT-treatment group. MLT did not significantly affect cell growth or death in cIECs compared to the CON. However, MLT treatment led to an upregulation of CD40, ZAP70, and IL7R and a downregulation of LCK, RPL37, TNFRSF13B, CD4, CD40LG, BLNK, and CIITA at the mRNA expression level. Moreover, MLT significantly altered the NF-kappa B signaling pathway by upregulating genes, such as CD40, ZAP70, TICAM1, VCAMI, GADD45B, IRAK1, TRADD, RELA, RIPK1, and RELB, and downregulating PRKCB, LY96, CD40LG, ILIB, BLNK, and TNFRSF11A. Using ChIP-qPCR, we discovered that MLT treatment enhanced histone acetylation marks H3K9ac, H3K18ac, H3K27ac, and methylation marks H3K4me1 and H3K4me3 at the ZAP70 and CD40 gene loci (p < 0.05). Additionally, the enrichment of RNA polymerase II and phosphorylated Ser5 pol-II at these loci was increased in MLT-treated cells (p < 0.05), indicating heightened transcriptional activity. In conclusion, our findings suggest that MLT mitigates inflammation in cIECs by modulating the transcription of ZAP70 and CD40 through histone modifications, offering potential therapeutic insights for inflammatory bowel diseases.